Enhancement of surface appearance of wood products in wood working industry has been done by application of wood stain. However, the use of wood stains has been recently limited due to emission of a hazardous material. Through this work a new technique of ammonia fuming has been experimented. The purpose of the research work was to investigate the effect of ammonia fuming and wood characteristics on the surface appearance of nangka wood (Artocarpus heteropyllus). The experimental result show - Wayan DARMAWAN; Istie S RAHAYU; Dodi NANDIKA; Widyana LUZA (Jurnal Ilmu dan Teknologi Hasil Hutan, 2011)
Enhancement of surface appearance of wood products in wood working industry has been done by application of wood stain.  However, the use of wood stains has been recently limited due to emission of a hazardous material.  Through this work a new technique of ammonia fuming has been experimented.  The purpose of the research work was to investigate the effect of ammonia fuming and wood characteristics on the surface appearance of nangka wood (Artocarpus heteropyllus).  The experimental result showed that ammonia in the volume of 2 liter could change significantly the natural color of (16 x 8 x 2) cm size nangka wood after 24 hours of fuming.  Increasing in the period of fuming to 48 hours did not provide any difference in color compared to the 24 hours of fuming, however the 48 hours fuming generated deeper changes in color on the surfaces of the wood.  Heartwood of nangka was observed to generate more significant changes in color compared to the sapwood.  Fresh wood produced a darker color than air-dried wood.  The wood treated by ammonia fuming showed an increase in resistance against termite and decayed fungi attacks.   Keywords   :  ammonia fuming, finishing, heartwood and sapwood, preservation